Structural and thermodynamic studies of two centrin isoforms from Blastocladiella emersonii upon calcium binding - Camargo, Ana I. (2013)
Centrins are calcium-binding proteins associated with microtubules organizing centers. Members of two divergent subfamilies of centrins were found in the aquatic fungus Blastocladiella emersonii, contrasting with the occurrence of only one member known for the better explored terrestrial fungi. BeCen1, shows greatest identity with human centrins HsCen1, HsCen2 and green algae centrin CrCenp, while BeCen3 records largest identity with human centrin HsCen3 and yeast centrin Cdc31p. Following the discovery of this unique feature, BeCen1 and BeCen3 centrins were produced to study whether these proteins had distinct features upon calcium binding. Circular dichroism showed opposite calcium binding effects on the alpha-helix arrangement of the secondary structure. The spectra indicated a decrease in alpha-helix signal for holo-BeCen1 contrasting with an increase for holo-BeCen3. In addition, only BeCen1 refolds after being denatured. The fluorescence emission of the hydrophobic probe ANS increases for both proteins likely due to hydrophobic exposure, however, only BeCen1 presents a clear blue shift when calcium is added. ITC experiments identified four calcium binding sites for both proteins. In contrast to calcium binding to BeCen1, which is mainly endothermic, binding to BeCen3 is mainly exothermic. Light-scattering evidenced the formation of large particles in solution for BeCen1 and BeCen3 at temperatures above 30°C and 40°C, respectively. Atomic force microscopy confirmed the presence of supramolecular structures, which differ in the compactness and branching degree. Binding of calcium leads to different structural changes in BeCen1 und BeCen3 and the thermodynamic characteristics of the interaction also differ.